The motion equation of turbine blade by the finite element method - Tin, Trinh Van (Vietnam Journal of Mechanics, 1993)
In this paper, the finite element method has been applied to deriving the motion equation of turbine blade in coupled bending - bending - torsion vibrations. These equations permit us to develop straightforwardly digital computer programs for studying vibration problems of turbine blades in turbo machinery as well as in other structural dynamic applications.